HUBUNGAN ASUPAN PROTEIN DAN ZAT BESI DENGAN STATUS ANEMIA PADA IBU HAMIL DI DESA NAGA TIMBUL KECAMATAN TANJUNG MORAWAKABUPATEN DELI SERDANG TAHUN 2014 - Eliani Sinaga; Zulhaida Lubis; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Anemia of pregnant women in Desa Naga Timbul is the effect of iron deficiency that relates with protein intake. There are some factors that affect anemia they are the less of protein intake, iron deficiency, lack of vitamin C, and absorption nuisance of intestine. Iron absorption is affected by some factors such as animal protein and vitamin C. The research is conducted in cross sectional design. The sample is 40 pregnant women. The objective of study is to find the relationship between protein intake and iron intake with anemia status of pregnant women in Desa Naga Timbul Kecamatan Tanjung Morawa Kabupaten Deli Serdang in 2014. The hemoglobin measurement is done by using Cyanmethemoglobin method and by using Spektrofotometer. Protein intake and iron intake are measured by food recall method in 24 hours twice in different days.. The relationship between protein intake and iron intake with anemia status is analyzed by Chi Square test. The result of the research shows that the less of protein intake category is 60.0 %, iron deficiency category is 72.5% and anemia is 55%. It shows that there is a significant relationship between protein intake and anemia status of pregnant women. The relationship between iron intake and anemia status of pregnant women is also significant. Based on the research, the pregnant women are expected to set up their time of eating better, to mull over the kinds of food that they consume and the nutrients of their foods in order to fulfill their needs of nutrients. In order to fulfill their needs of protein and iron, the families are expected to use their house environment for instance raise chicken and fish, plant vegetable around their house. Keywords: Protein intake, Nutritional anemia, Pregnant women